1991
DOI: 10.1007/bf00127244
|View full text |Cite
|
Sign up to set email alerts
|

Meiotic behavior of Robertsonian heterozygotes in populations of Dichroplus pratensis (Acrididae) with different fusion frequencies

Abstract: The meiotic behavior of Robertsonian heterozygotes of Dichropluspratensis was analyzed in order to establish the nature of the fusion polymorphisms (stable or transient) that occur in the species. The range of fusion frequencies varies widely for each fusion studied and populations with extreme frequencies exist, which could indicate a tendency for the loss or fixation of a given rearrangement. Our results revealed that no significant correlation exists between orientation (convergent and non-convergent) in PM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Maintenance of such balanced polymorphisms is only possible if meiotic behaviour of trivalents in heterozygotes is regular (unless heterozygotes are positively heterotic despite loss of fertility due to meiotic misbehaviour). We have shown that all heterozygous fusions behave well at meiosis (Bidau and Mirol, 1988;Mirol and Bidau, 1991a) as demonstrated by their very low non-convergent orientation frequencies and production of abnormal sperm. However, aneuploidy and macrospermatid production increase with the number of heterozygous fusions (Bidau and Mirol, 1988) which could explain the higher frequencies of fusion metacentrics in populations with 3 fusions in order to minimise the frequencies of double and triple heterozygotes (Tosto, 1989;Tosto and Bidau, 1991).…”
Section: Introductionmentioning
confidence: 93%
“…Maintenance of such balanced polymorphisms is only possible if meiotic behaviour of trivalents in heterozygotes is regular (unless heterozygotes are positively heterotic despite loss of fertility due to meiotic misbehaviour). We have shown that all heterozygous fusions behave well at meiosis (Bidau and Mirol, 1988;Mirol and Bidau, 1991a) as demonstrated by their very low non-convergent orientation frequencies and production of abnormal sperm. However, aneuploidy and macrospermatid production increase with the number of heterozygous fusions (Bidau and Mirol, 1988) which could explain the higher frequencies of fusion metacentrics in populations with 3 fusions in order to minimise the frequencies of double and triple heterozygotes (Tosto, 1989;Tosto and Bidau, 1991).…”
Section: Introductionmentioning
confidence: 93%
“…Orientation of Rb multivalents is conditioned by the distance between centromeres, which in turn depends on the size of the involved chromosomes and the localization and frequency of chiasmata, which determine the symmetry of the configuration (Narasinga Rao and Sybenga 1984; Arundhati et al 1986; Bidau 1991, 1996; Mirol and Bidau 1991; Bidau and Martí 1995). …”
Section: Factors Affecting Meiotic Orientation Of Rb Multivalentsmentioning
confidence: 99%
“…Evidently, in these cases, the depressing effects of structural heterozygosis on fitness are somehow suppressed. In fact, when trivalent orientation is studied, convergent orientation is the norm and linear orientation the exception (Bidau and Mirol 1988; Mirol and Bidau 1991, 1992; Colombo 2009). …”
Section: Chiasma Redistribution Due To Rb Polymorphismsmentioning
confidence: 99%
“…In some cases, such meiotic configurations arise from nonchiasmate interactions between C-band positive ends and either euchromatic ends or other heterochromatic blocks of non-homologues (Drets and Stoll, 1974;John andKing, 1982, 1985). On the other hand, several studies have shown multivalent configurations at first meiosis as a result of heterozygosity for either interchange or Robertsonian fusion or fission (John, 1987;Bidau and Mirol, 1988;Haaf et al, 1989;Moss and Murray, 1990;Mirol and Bidau, 1991, 1994Reed et al, 1992). In all these cases, the associations between non-homologues were chiasmate.…”
Section: Introductionmentioning
confidence: 99%